AB0791 Case-not audit of the management of polymyalgia rheumatica. (23rd January 2014) - Zhao, S.; Abrahams, A.; Goodson, N.; Anderson, M.
Abstract : Background: Polymyalgia rheumatica (PMR) is a common condition with an incidence of about 100 per 100, 000 in those aged over 50. There is heterogeneity in presentation, response to steroids and disease course. There is also little communication between primary and secondary care as only a small proportion is under shared care. These factors contribute to the lack of standardisation in management: The British Society of Rheumatology (BSR) published guidelines in 2009 to standardise this. Objectives: The objective of this audit was to evaluate the quality of management of PMR at Aintree hospital's rheumatology department (Liverpool, UK)using standards set around aspects of BSR guidelines. Methods: A cohort of 98 patients with a diagnosis of PMR between Jan 2007 and Nov 2010 were identified from outpatient clinical letters. Based on BSR guidelines, a questionnaire was designed and used to gather data. It assessed: 1) Documentation of clinical criteria and laboratory investigations which forms the basis for the diagnosis; 2) Usage of tapering steroid therapy; 3) Use of bone protection; 4) Clinical and biochemical monitoring of response to treatment and disease activity; 5) Management of relapses. All clinical letters, case notes and investigations were studied from electronic records or paper case notes. Results: 1) Initial assessment investigations: in 97% of patients clear documentation recorded clinical criteria and baseline blood tests. However, serum electrophoresis, Bence-Jones protein, CK and anti-CCP were requested in <50% of cases. 2) Starting dose of Prednisolone: This varied between departments. When started by a rheumatologist, 94% were given the recommended 15mg. However, 59% were initiated on treatment by GPs or general physicians and the mean starting dose in this subgroup was 23.6mg (SD 11.2mg). 3) Steroid tapering: 35% were prescribed tapering regimes similar to that recommended by BSR. 22% had no clear instructions of steroid tapering regimes. 36% were weaned too quickly off steroids. Those patients weaned off steroids in <1 year had 39% flare rate, whilst those weaned off >1 year had a flare rate of 19%. 3) Bone protection: bone protection with bisphosphonate, calcium and vitamin D were co-prescribed in 81%. 4) Clinical response to treatment was documented in 99% and biochemical monitoring was documented in 66%. Side effects of treatment were recorded in 27%. 5) Relapse management was documented clearly in 22% and DMARDs were considered in 6 of the 10 patients that experienced >2 relapses. Conclusions: This audit has highlighted that management of PMR in rheumatology clinics is generally at high standard. However, education of other specialities about optimum prednisolone start doses and the importance of bone protection are needed. The observation that rapid steroid tapering is associated with high flare rates is important in this patient group. In light of this we have developed a standard prednisolone withdrawal regime for PMR in attempt to reduce the frequency of PMR flares. References: BSR and BHPR guidelines for the management of polymyalgia rheumatica B Dasgupta, et al. BSR and BHPR guidelines for the management ofpolymyalgia rheumatica, 2009 Disclosure of Interest: None Declared